Metabolic changes reveal the development of schistosomiasis in mice. - Junfang Wu; Wenxin Xu; Zhenping Ming; Huifen Dong; Huiru Tang; Yulan Wang (Public Library of Science (PLoS), 2010)
Schistosomiasis is a parasitic zoonosis caused by small trematode worms called schistosomes, amongst which Schistosoma japonicum (S. japonicum) is endemic in Asia. In order to understand the schistosome-induced changes in the host metabolism so as to facilitate early diagnosis of schistosomiasis, we systematically investigated the dynamic metabolic responses of mice biofluids and liver tissues to S. japonicum infection for five weeks using (1)H NMR spectroscopy in conjunction with multivariate data analysis. We were able to detect schistosomiasis at the third week post-infection, which was one week earlier than "gold standard" methods. We found that S. japonicum infection caused significant elevation of urinary 3-ureidopropionate, a uracil catabolic product, and disturbance of lipid metabolism, stimulation of glycolysis, depression of tricarboxylic acid cycle and disruption of gut microbiota regulations. We further found that the changes of 3-ureidopropionate and overall metabolic changes in both urinary and plasma samples were closely correlated with the time-course of disease progression. Furthermore, such changes together with liver tissue metabonome were clearly associated with the worm-burdens. These findings provided more insightful understandings of host biological responses to the infection and demonstrated that metabonomic analysis is potentially useful for early detection of schistosomiasis and comprehension of the mechanistic aspects of disease progression.